2020
DOI: 10.1007/s11883-020-00888-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Vital Function and Malfunction of Serum Amyloid A: an Acute-Phase Protein that Wears Hydrophobicity on Its Sleeve

Abstract: Purpose of Review This review addresses normal and pathologic functions of serum amyloid A (SAA), an enigmatic biomarker of inflammation and protein precursor of AA amyloidosis, a life-threatening complication of chronic inflammation. SAA is a small, highly evolutionarily conserved acute-phase protein whose plasma levels increase up to one thousand-fold in inflammation, infection, or after trauma. The advantage of this dramatic but transient increase is unclear, and the complex role of SAA in immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 105 publications
0
17
0
Order By: Relevance
“…Frontiers in Marine Science | www.frontiersin.org acute inflammatory response, with a significant enhancement of serum CRP and SAA levels following organism inflammation, injury, or infection (Pepys et al, 1978;Lindhorst et al, 1997;Pepys and Hirschfield, 2003;MacCarthy et al, 2008;Rosani et al, 2016;Franco-Martinez et al, 2019;Bello-Perez et al, 2020;Gursky, 2020;Williams et al, 2020). Derebe et al (2014) reported that vitamin A deficiency may lead to an immune deficiency in mice with decreasing the abundances of SAAs in small intestine and liver.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Marine Science | www.frontiersin.org acute inflammatory response, with a significant enhancement of serum CRP and SAA levels following organism inflammation, injury, or infection (Pepys et al, 1978;Lindhorst et al, 1997;Pepys and Hirschfield, 2003;MacCarthy et al, 2008;Rosani et al, 2016;Franco-Martinez et al, 2019;Bello-Perez et al, 2020;Gursky, 2020;Williams et al, 2020). Derebe et al (2014) reported that vitamin A deficiency may lead to an immune deficiency in mice with decreasing the abundances of SAAs in small intestine and liver.…”
Section: Discussionmentioning
confidence: 99%
“…Serum amyloid A (SAA) consists of a family of proteins that share a high degree of homology, encoded by genes highly conserved throughout evolution. In humans, there are 4 SAA genes, but only saa1 and saa2 encode acute phase proteins, highly inducible during the acute phase response [ 61 , 62 ]. Due to its high hydrophobicity, only a small fraction of SAA is present in plasma in a lipid-free form.…”
Section: Serum Amyloid a (Saa)mentioning
confidence: 99%
“…It forms the amyloid senescence cascade hypothesis and is harmful to the non-senescent surrounding cells [111]. "Secondary" amyloidosis due to the serum amyloid A proteins is of lysosomal origin [112].…”
Section: Amyloidosismentioning
confidence: 99%